2018
DOI: 10.3390/ijms19113386
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Anticonvulsant Effects of Novel Histamine H3R Antagonists in Electrically and Chemically Induced Seizures in Rats

Abstract: A newly developed series of non-imidazole histamine H3 receptor (H3R) antagonists (1–16) was evaluated in vivo for anticonvulsant effects in three different seizure models in Wistar rats. Among the novel H3R antagonists examined, H3R antagonist 4 shortened the duration of tonic hind limb extension (THLE) in a dose-dependent fashion in the maximal electroshock (MES)-induced seizure and offered full protection against pentylenetetrazole (PTZ)-induced generalized tonic-clonic seizure (GTCS), following acute syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…However, no protective effect was observed following pretreatment with E177 (2.5 and 15 mg/kg), indicating a dose-dependent effect of E177 in PLC-induced seizure model. The latter dose-dependent effect of E177 is in agreement with previous preclinical outcomes that demonstrated a dose-dependent effect of different H3R antagonists in several animal models [23,25,30], and with our previous observation of a dose-dependent anticonvulsant effect of E177 in electrical as well as chemically induced seizure models [28]. Importantly, the protection provided by E177 (5 and 10 mg/kg) in the PLC-induced seizure model was significantly higher when compared to the higher dose (15 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, no protective effect was observed following pretreatment with E177 (2.5 and 15 mg/kg), indicating a dose-dependent effect of E177 in PLC-induced seizure model. The latter dose-dependent effect of E177 is in agreement with previous preclinical outcomes that demonstrated a dose-dependent effect of different H3R antagonists in several animal models [23,25,30], and with our previous observation of a dose-dependent anticonvulsant effect of E177 in electrical as well as chemically induced seizure models [28]. Importantly, the protection provided by E177 (5 and 10 mg/kg) in the PLC-induced seizure model was significantly higher when compared to the higher dose (15 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, numerous H3R antagonists were previously investigated on their protective effects in different acute seizure models, and the results revealed their anticonvulsant effects [23,30,42,43,44,45,46,47]. In this study and as a continuation of our previous work, the protective effect of the non-imidazole based H3R antagonist E177 with high in vitro antagonist affinity ( h H3R K i = 69.3 nM) [36,37] and excellent selectivity profile [28] towards H3Rs was investigated in the PLC-induced SE model. Supported by the behavioral and morphological outcomes as well as electroencephalographic waves observed in previous preclinical studies, the PLC-induced seizure model has been proposed as an animal model with similarity in characteristics to TLE, and numerous previous studies showed that acute systemic administration of a high dose of the muscarinic cholinergic agonist PLC (400 mg/kg) provoked behavioral alternations and convulsions in all tested animals which developed within 30 min to SE [8,9,11,48,49,50].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, we have documented the protective effect of E177, a potent non-imidazole H3R antagonist/ inverse agonist, in MES-and PTZ-induced seizure models, with E177 (10 mg/kg i.p.) showing the most promising anticonvulsant effect [31]. Also, E177 (5 mg/kg i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…137 Furthermore, an increase in the bioavailability of biogenic amines due to DAO or iNOS inhibition improves their vasoactive activity and they can reach the central nervous system in different possible ways to alter the nervous centres. [138][139][140][141][142] Some of the impairments are seizures and tremors through histamine H3R receptors 143 and polyamines NMDA receptors. 144 Additional pro-convulsive mechanisms for NOS2 will be discussed in next sections.…”
Section: Participation In Neurological Balance and Nervous Ac-mentioning
confidence: 99%